PHARMACOECONOMIC STUDY OF SKIN TESTS IN THE DIAGNOSTICS OF TUBERCULOSIS INFECTION - R. I. Yagudina; I. Yu. Zinchuk (Фармакоэкономика)
To provide pharmacoeconomic evaluation of diagnostics of tuberculosis infection (TI) with Allergen tuberculosis recombinant (CFP10-ESAT6) and Allergen tuberculosis purified liquid in the standard dilution for intradermal use (PPD RT 23 SSI). The «cost-effectiveness» analysis was provided. In the study direct costs were considered. Finally, total direct costs for the diagnostics one patient with active tuberculosis were 122.687 RUR, 3.646.833 RUR and 551.150 RUR, for the estimated diagnostic schemes, respectively. The pharmacoeconomic study results have shown, that a CFP10-ESAT6 is dominant technology from «cost-effectiveness» analysis perspective.